Bringing next‐generation diagnostics to the clinic through synthetic biology. Issue 9 (11th July 2016) - Courbet, Alexis; Renard, Eric; Molina, Franck
Abstract : The promise for real precision medicine is contingent on innovative technological solutions to diagnosis and therapy. In the post‐genomic era, rational and systematic approaches to biological design could provide new ways to dynamically probe, monitor, and interface human pathophysiology. Emerging as a mature field increasingly transitioning to the clinics, synthetic biology integrates engineering principles to build sensors, control circuits, and actuators within the biological substrate according to clinical specifications. A particularly tantalizing goal is to develop novel versatile, programmable and autonomous diagnostic devices intertwined with therapy and personalized for the patient to get closest, finest, and most comprehensive diagnostic information and medical procedures. Here, we discuss how synthetic biology could be preparing the future of medicine, supporting and speeding up the development of diagnostics with novel capabilities to bring direct improvement from the clinical laboratory to the patient, while addressing healthcare evolution and global health concerns. Abstract : Courbet, Renard and Molina comment on the prospects of precision medicine and how synthetic biology could be preparing the future of medicine by providing innovative technological solutions to diagnosis and therapy.